IMMU-47. HARNESSING ZIKA VIRUS (ZIKV) ONCOLYTIC ACTIVITY IN BRAIN TUMORS. (5th November 2018) - Jash, Arijita; Govero, Jennifer; Shi, Pei-Yong; Rich, Jeremy; Diamond, Michael S; Chheda, Milan G
Abstract: Glioblastoma (GBM) is a highly lethal immunosuppressive brain cancer that contains glioblastoma stem-like cells (GSCs). GSCs are at least partly responsible for tumor maintenance, progression, recurrence and resistance and are thus potential therapeutic targets. ZIKV, a flavivirus, preferentially infects and kills glioblastoma stem cells (GSCs) compared to differentiated tumor progeny and normal neural cells (Zhu, Z. et al. Zika virus has oncolytic activity against glioblastoma stem cells. J. Exp. Med.2017). We are actively investigating if ZIKV-mediated tumor clearance is dependent on the dual mechanism of action of selective tumor cell killing and the induction of systemic anti-tumor immunity. In anticipation of possible clinical use of ZIKV as a GSC therapy, we have introduced mutations in the ZIKV genome that will (1) prevent 2-'O methylation of viral RNA and render it sensitive to inhibition by IFIT1, (2) prevent the generation of non-coding subgennomic (sfRNA) viral RNA that antagonizes type I IFN immunity, (3) limit viral dissemination, and (4) make reversion to the pathogenic virus a highly unlikely event. We are in the process of testing in vivo the efficacy of tumor killing and control of these modified viruses, compared to the parental control. Additionally, we are investigating the effect of ZIKV in controlling patient-derived GSCs in vivo using NSG (non-obese diabetic severe combined immune deficiency, IL2Rγ-null) mice. Lastly, we will present preliminary data on ZIKV treatment followed by immune checkpoint blockade. These findings will further advance the potential use of ZIKV in GBM oncolytic virotherapy.